Characterization of organic composts produced by family farming for lettuce cultivation - Bertani, Rosemary Marques de Almeida; Cecília de Arruda, Maria; Cristina Fernandes Deus, Angélica; Herman Fischer, Ivan; Rossi , Renan; Augusto Maganhã, Carlos (Comunicata Scientiae, 2022)
The use of organic compost in the cultivation of lettuce by family farming can be carried out in a sustainable way with the use of residues from the property, through composting. For efficient and safe use of these residues, it is necessary to monitor the composting process and adopt good agricultural practices for the production of safe food. Therefore, the objective was to identify and quantify contaminating microorganisms and to evaluate the chemical characteristics of organic compounds and their effects on the cultivation of lettuce produced in an organic system. Six periods of lettuce cultivation were studied using the organic compost produced in the planting fertilizer and cover. The results obtained for the fresh mass and the chemical analyzes of the compost, the soil and the plant were compared in a qualitative way. The results obtained from microbiological analyzes were compared to current legislation. The composition of the material used and the handling of the composting process influenced the chemical characteristics of the organic compounds applied to the soil. Organic compounds were efficient for plant nutrition, except for boron. The presence of thermotolerant coliforms was above the maximum acceptable limit, indicating contamination of the compound. The organic compost was not properly composted in most cycles. The use of organic compounds proved to be a sustainable alternative in the production of organic lettuce on family farms, but the study indicated the need for technical training.